Anatomical variations of hepatic arteries: implications for clinical practice - Samuolyte, Austeja; Luksaite-Lukste, Raminta; Kvietkauskas, Mindaugas (Frontiers in Surgery, 2025)
Variations in hepatic arterial anatomy are highly prevalent, occurring in 45% to 75% of individuals. Understanding hepatic arterial anatomy is critical in optimizing surgical outcomes in hepatopancreatobiliary surgery, transplantation, and interventional radiology. Aberrant arteries are prone to accidental injury during surgery, which may lead to life threatening complications, such as hemorrhage or ischemia. Therefore, a clear understanding of hepatic arterial anatomy is essential for reducing intraoperative risk and improving surgical outcomes. To address this need, the present review provides an overview of hepatic arterial variants according to Michel's classification, aiming to enhance anatomical awareness and contribute to improved procedural planning across disciplines.